Drogas como dispositivo, crack como atravessamento: as (necro)políticas de internação involuntária - Carolina Maria Nasser Cury (2022)
This thesis aims to address the contemporary scope of the involuntary hospitalization of crack users in the logic of rationality. Therefore, I studied the emergence of prohibitionism and social medicine, based on the analysis of the prohibition of drugs as a construct, its criminalization movements, the ways in which treatment of drug addiction has been addressed through time and, finally, the legal stipulations forged around the legal management of drug consumption. Subsequently, I approached the crack issue, inquiring about its emergence, its effects, its agencies and its territorialities. Then, I presented the way in which the idea of danger, control and normalization articulate themselves with the differential distribution of precariousness, in order to frame them into the necropolitical scope of the involuntary hospitalization, highlighting the inefficiency of the involuntary scope of treatment and also the structure that provide the involuntary hospitalization as a growing theme in Brazilian contemporary scenario.